Calculation of Dynamic Characteristics of the Sample-and-Hold Circuit for Analog Information Converters - Marcinkevičius, A.; Jasonis, V. (Elektronika ir Elektrotechnika, 2004)
Generalized models of sample-and-hold circuits (SHC) for analog-to-digital information converters and methods of aperture errorcalculation are considered. Analytical equations for modeling the SHC aperture frequency characteristics depending on the dynamicparameters of strobe pulses and additive noises were designed. On the basis of calculation results of frequency characteristics, it isshown that the strobe pulse front duration and the noise amplitude have significant influence on the aperture error in the high-frequencyregion. The influence of the aperture uncertainty on the signal-to-noise ratio is most displayed in the high-frequency region when theanalog signal maximum frequency exceeds 10 MHz. To increase the signal-to-noise ratio, the aperture uncertainty and the electron keyinertness have to be reduced, the strobe pulse front steepness should be increased and the noise amplitude must be reduced. The obtainedmathematical expressions estimate the dependence of the SHC accuracy or the signal-to-noise ratio on the strobe pulse dispersion andthe correlation with strobe pulses. To increase the wide-band SHC accuracy, the layout architecture of the signal and strobe paths mustbe optimized in order to decrease the noise amplitude and aperture uncertainty. Ill. 4, bibl. 6 (in Lithuanian; summary in Lithuanian,English and Russian).